2005
DOI: 10.1002/mrc.1708
|View full text |Cite
|
Sign up to set email alerts
|

Free radicals in vicariousC-amination reactions of 1-methyl-4-nitropyrazole

Abstract: The primary radical anions of substrate in the reactions of vicarious nucleophilic substitution of hydrogen in 1-methyl-4-nitropyrazole with 1,1,1-trimethylhydrazinium iodide and 4-amino-1,2,4-triazole in t-BuOK-DMSO were observed and identified by EPR monitoring. The probable mechanism of the substrate radical anions formation is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The vicarious nucleophilic substitution of hydrogen was first used by V. A. Lopyrev, G. V. Dolgushin, and coworkers for the C-amination of N-methylnitroazoles by 1,1,1-trimethylhydrazinium halides 114 or 4H-1,2,4-triazole-4-amine 115 in superbasic media [299][300][301][302][303][304][305][306]. …”
Section: Pyrazoles Imidazoles Thiazoles and Oxazolesmentioning
confidence: 99%
“…The vicarious nucleophilic substitution of hydrogen was first used by V. A. Lopyrev, G. V. Dolgushin, and coworkers for the C-amination of N-methylnitroazoles by 1,1,1-trimethylhydrazinium halides 114 or 4H-1,2,4-triazole-4-amine 115 in superbasic media [299][300][301][302][303][304][305][306]. …”
Section: Pyrazoles Imidazoles Thiazoles and Oxazolesmentioning
confidence: 99%
“…We found the answer to this question by comparing the results from investigation of the vicarious C-amination of the nitro derivatives of 1,2,3-and 1,2,4-triazoles by ESR and the analogous results that we obtained earlier for 1-methyl-4-nitropyrazole [12], 1-methyl-4-nitroimidazole [9,10], and 1-methyl-5-and 1-methyl-6-nitrobenzimidazoles [11] with the data from quantum-chemical calculations of the spin density distribution in the radical-anions of the substrates a-i. It was found that the The calculated spin density at the CH carbon atoms in the radical-ions of nitroazoles amination of all the above-mentioned compounds takes place exclusively at carbon atoms with sufficiently high positive spin density in their radical-anions.…”
Section: _______mentioning
confidence: 85%
“…As expected, ESR monitoring showed that the reaction mixture of the N-unsubstituted nitrotriazole 6 with the iodide 2 was diamagnetic, and this agrees with the absence both of the blue-violet color in the reaction mixture and of the amination product. It was unexpectedly found that 1-methyltriazole 7, unlike other N-protected nitroazoles [10][11][12], also does not form amination products under the conditions of the vicarious nucleophilic substitution of hydrogen, although in this case the reaction mixture was colored, and a signal for the primary radical-anion of 1-methyl-3-nitro-1,2,4-triazole (g = 2.0032) appeared in the ESR spectrum with signals and HFS constants, mT: triplet (N-NO 2 , 1.178); doublet (1H, 0.440); triplet (1N, 0.160); triplet (1N, 0.120); triplet (1N, 0.050); quartet (3H-CH 3 , 0.050) (Fig. 2).…”
Section: _______mentioning
confidence: 96%
See 2 more Smart Citations